2020
DOI: 10.1016/j.heliyon.2020.e04211
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive effects of 2-methacryloyloxyethyl phosphorylcholine (MPC)-polymer on the adherence of Candida species and MRSA to acrylic denture resin

Abstract: The effects of 2-methacryloyloxyethyl phosphorylcholine (MPC)-polymer on the adherence of microorganisms such as non-Candida albicans Candida (NCAC) and methicillin-resistant Staphylococcus aureus (MRSA), frequently detected in oral infections in immunocompromised and/or elderly people, to denture resin material, are still unclear. Here, we report the effects of MPC-polymer on the adherence of C. albicans, NCAC, and MRSA to acrylic denture resin. Methods: Sixteen strains of C. albicans, seven strains of C. gla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 54 publications
3
11
0
Order By: Relevance
“…The authors concluded that the mechanical property of the thin-film is one of the influential factors determining bacterial adhesion. These findings would be of significance in designing antibacterial materials [16].…”
Section: Introductionmentioning
confidence: 76%
“…The authors concluded that the mechanical property of the thin-film is one of the influential factors determining bacterial adhesion. These findings would be of significance in designing antibacterial materials [16].…”
Section: Introductionmentioning
confidence: 76%
“…Although the positive impact of the MPC against salivary and single-species biofilms has been validated in multiple studies, detailed analysis of specific strains of the species has not been widely reported. A recent study evaluated C. albicans (16 strains), Non-C. albicans Candida (NCAC; 10 strains) and Methicillin-resistant Staphylococcus aureus (MRSA; six strains) resistance of the MPC-polymer-coated, acrylic, denture plates [93]. The microbial adherence was tested on the mucin-coated specimens by comparing the cell hydrophobicity.…”
Section: Removable Appliancesmentioning
confidence: 99%
“…Some pH-triggered dynamic bonds, such as benzoxaboronic ester, hydrazine, and imine bonds, have been applied to designing intelligent nanocarriers with pH responsiveness. , The aromatic imine bond has advantages for constructing BCP micelles with sensitive pH-responsiveness due to its rapid cleavage upon external pH stimulation. , Moreover, there are strong hydrophobic interactions and π–π stacking from multiaromatic groups, which can significantly improve the stability of micelles against harsh physiological environment. , Zwitterionic MPC-based polymers have been proven to be highly biocompatible biomaterials (Food and Drug Administration (FDA)-approved) that can resist nonspecific protein adsorption and maintain long-time stability in plasma. Moreover, zwitterionic poly­(MPC) (PMPC) in conjugation with therapeutic proteins, such as interferon and antibodies, has demonstrated evident pharmacokinetic enhancement and epitope specificity. , By combining the advantages of aromatic imine bonds and zwitterionic polymers, well-structured BCP micelles were developed from the self-assembly of a zwitterionic block copolymer, poly­(2-methacryloyloxyethyl phosphorylcholine- b -poly­(di­(ethylene glycol) methyl ether methacrylate- co -4-formylphenyl methacrylate) [PMPC- b -P­(DEGMA- co -FPMA), BCP], which was synthesized by RAFT polymerization. As shown in Scheme , the FPMA components in BCP with reactive aldehyde groups provide a suitable capability for covalently conjugating with TPZD (containing an amine group) to give a hypoxia-activated BCP-TPZ conjugate through the formation of imine bonds.…”
Section: Introductionmentioning
confidence: 99%